The Spatial Division of Labor in Nepal - Fafchamps, Marcel; Shilpi, Forhad (World Bank, Washington, D.C., 2013)
the authors examine how economic activity and market participation are distributed across space. Applying a nonparametric von Thunen model to Nepalese data, the authors uncover a strong spatial division of labor. Nonfarm employment is concentrated in and around cities, while agricultural wage employment dominates villages located further away. Vegetables are produced near urban centers. Paddy and commercial crops are more important at intermediate distances. Isolated villages revert to self-subsistence. The findings of the study are consistent with the von Thunen model of concentric specialization, corrected to account for city size. Spatial division of labor is closely related to factor endowments and household characteristics, especially at the local level.